The role of point-of-care ultrasound (POCUS) imaging in clinical outcomes during cardiac arrest: a systematic review - Hany A. Zaki; Haris Iftikhar; Eman E. Shaban; Mavia Najam; Baha Hamdi Alkahlout; Nabil Shallik; Wael Elnabawy; Kaleem Basharat; Aftab Mohammad Azad (The Ultrasound Journal, 2024)
Abstract Background Cardiac arrest in hospital and out-of-hospital settings is associated with high mortality rates. Therefore, a bedside test that can predict resuscitation outcomes of cardiac arrest patients is of great value. Point-of-care ultrasound (POCUS) has the potential to be used as an effective diagnostic and prognostic tool during cardiac arrest, particularly in observing the presence or absence of cardiac activity. However, it is highly susceptible to “self-fulfilling prophecy” and is associated with prolonged cardiopulmonary resuscitation (CPR), which negatively impacts the survival rates of cardiac arrest patients. As a result, the current systematic review was created to assess the role of POCUS in predicting the clinical outcomes associated with out-of-hospital and in-hospital cardiac arrests. Methods The search for scientific articles related to our study was done either through an electronic database search (i.e., PubMed, Medline, ScienceDirect, Embase, and Google Scholar) or manually going through the reference list of the relevant articles. A quality appraisal was also carried out with the Quality Assessment of Diagnostic Accuracy Studies tool (QUADAS-2), and the prognostic test performance (sensitivity and sensitivity) was tabulated. Results The search criteria yielded 3984 articles related to our topic, of which only 22 were eligible for inclusion. After reviewing the literature, we noticed a wide variation in the definition of cardiac activity, and the statistical heterogeneity was high; therefore, we could not carry out meta-analyses. The tabulated clinical outcomes based on initial cardiac rhythm and definitions of cardiac activity showed highly inconsistent results. Conclusion POCUS has the potential to provide valuable information on the management of cardiac arrest patients; however, it should not be used as the sole predictor for the termination of resuscitation efforts.